2022
DOI: 10.3390/jcm11071915
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin 1 Regulates Inflammatory Mediators and Reactive Oxygen Species in Retinal Endothelial Cells

Abstract: Diabetic retinopathy is associated with increased inflammatory mediator levels. In these studies, we focused on prohibitin 1. We performed western blotting for retinal lysates from diabetic mice and Epac1 floxed and cdh5Cre-Epac1 mice. We also grew primary retinal endothelial cells (REC) in normal (5 mM) and high (25 mM) glucose, and treated some cells with an Epac 1 agonist or prohibitin 1 siRNA. Western blotting was done to confirm knockdown of prohibitin 1 and Epac 1 agonism. We measured the tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the underlying mechanisms are still unclear. Some reports have shown that Epac1 regulates intercellular adhesion, links, and the vascular endothelial permeability after injury ( 24 , 25 ). Various effector proteins are the signals downstream from Epac1.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanisms are still unclear. Some reports have shown that Epac1 regulates intercellular adhesion, links, and the vascular endothelial permeability after injury ( 24 , 25 ). Various effector proteins are the signals downstream from Epac1.…”
Section: Introductionmentioning
confidence: 99%